Low basal serum testosterone level is detrimental to the embryo implantation in the patients with severe endometriosis. Issue 6 (5th April 2021) - Huang, Ling; Chen, Minghui; Long, Lingli; Tuo, Ying; Wang, Zengyan; Zhou, Canquan; Li, Yubin
Abstract: Aim: Androgens have been reported to be associated with female fertility. The mean serum testosterone concentration in the patients with endometriosis was reported to be significantly lower than that without endometriosis. Our study was designed to investigate the influence of basal serum testosterone levels on the clinical outcome of in vitro fertilization (IVF) in the patients with III‐IV stage endometriosis. Methods: This retrospective cohort study included 407 patients with III‐IV stage endometriosis diagnosed by laparoscopic surgery. We studied the association of the basal serum testosterone level and the reproductive outcome of IVF. Results: The basal serum testosterone concentration was significantly higher in the pregnant group of patients with III‐IV stage endometriosis. The further analyses demonstrated that the implantation rate of the basal serum testosterone concentration < 0.305 ng/mL group was significantly lower than the testosterone ≥ 0.305 ng/mL group (24.1% vs. 32.7%, p = 0.007). The clinical pregnancy and live birth rate of the basal serum testosterone < 0.305 ng/mL group were also lower than that of the testosterone ≥ 0.305 ng/mL group. Both initial and total dose of gonadotropins in the testosterone <0.305 ng/mL group are significantly higher than that of the testosterone ≥0.305 ng/mL group. Conclusions: Our study demonstrated, for the first time, that the basal serum testosterone <0.305 ng/mL had an adverse impact on pregnancy outcomes of IVF‐embryo transfer in the patients with III‐IV stage endometriosis. Besides, the basal serum testosterone is also helpful in making individual stimulation protocol for the patients with advanced endometriosis before entering IVF cycles.